Beyond the Screen: Re-evaluating Non-Verbal Cues in Digital-Age Communication - Timilsina, Bedhari (AWADHARANA, 2025)
The massive shift to digital communication (e.g., text, video, VR) has fundamentally altered interpersonal interaction, creating a significant challenge where crucial non-verbal cues (NVCs) like body language and tone are often weakened or obscured. This systematic loss of NVCs is a major concern, as they are essential for conveying emotions, building trust, and preventing misunderstandings. This paper aims to analyze the persistent role and impact of NVCs in the digital age and propose strategies for effective communication. Using a deductive approach and reviewing academic literature from 2015-2024, the study examined how various digital platforms constrain the transmission of NVCs. Findings confirmed that this "non-verbal cue gap" contributes to misinterpretation, reduced social presence, and phenomena like "Zoom fatigue." While platforms like VR offer potential for richer non-verbal exchange, basic media (like text) still rely on inadequate digital substitutes (e.g., emojis). The study concludes that the weakening of NVCs poses a threat to empathetic connection. The primary implication is the critical need for individuals and organizations to adopt a strategic and balanced communication approach, prioritizing high-richness channels for complex interactions and actively promoting non-verbal literacy to preserve genuine human connections in an increasingly digital world.